COINCIDENCE OF MAPS ON TORUS FIBRE BUNDLES OVER THE CIRCLE - Vieira, Joao Peres [UNESP] (Juliusz Schauder Ctr Nonlinear Studies, 2015)
The main purpose of this work is to study coincidences of fibre preserving self-maps over the circle S-1 for spaces which are fibre bundles over S' and the fibre is the torus T. We classify all pairs of self-maps over S-1 which can be deformed fibrewise to a pair of coincidence free maps.
Keywords: Coincidence; fibre bundle; fibrewise homotopy